Midwifery students’ perception on learning facilities and their motivation to learn - Suci Fitriana Pramudya Wardani (International Journal of Health Science and Technology, 2020)
Learning motivation is the trigger in a student’s self which causes, maintains, and directs learning activities to specific target. Motivation plays a very important role in a student’s advancement and development through learning process.    The objective of the research was to find out the correlation between students’ perception on learning facilities and their motivation to learn at Midwifery Academy of Doctor Rusdi Foundation, in 2014. The research was an analytic survey. The samples were 72 students as respondents, using total population technique. The result of the research, using chi square test at the reliability level of 95%, showed that p-value (0.000) α -0.05 which indficated that there was the correlation between students’ perception on learning facilities and their motivation to learn at Midwifery Academy of Doctor Rusdi Foundation, Medan, in 2014. Conclusion of the research was that there was the correlation between students’ perception on learning facilities and their motivation to learn at Midwifery Academy of Doctor Rusdi Foundation, Medan. It is recommended that the management of Midwifery Academy of Doctor Rusdi Foundation, Medan, provide complete teaching facilities so that students’ motivation will increase, which will eventually influences their learning performance because good learning performance indicates their achieving competence.